Korban penyalahgunaan rezim orde baru - Sri Hartini (Jurnal Civics: Media Kajian Kewarganegaraan, 2007)
Abuse of power committed by the New Order regime covered all aspects of life, including legal aspects, economic and political. As a result in legal field, the abuse caused the victim of individuals, groups and citizens who suffered physicaIIY, mentallY, and economicallY. People (''grassroots'') and the country became a victim of abuse of power committed by the rulers of the New Order in the economicfield Further consequences of abuse of power committed by the New Order regime in the political casualties of individuals, groups, communities and social structures that stiffered phisicallY, mentallY and economicallY. Victims of abuse of power of the New Order regime that includes a new victim (new victimology) is positive in the criminal law was not identified by authorities as a victim, as victims of conventional crime which is the target of criminal law in Indonesia. Victims of abuse of power, including victims of crimes, are unconventional. Viewed from the paradigm of victimization, the victims of abuse of power includes politzcal.